The effect of physical activity on the skeletal maturity of the wrist bone and cervical vertebra of children: SPORTS AND BONE DEVELOPMENT - Duran, Bulent; Sadry, Sanaz (Progress in Nutrition, 2021)
Regular physical activity, participation in sports or training is known to have effect on growth-development. The aim of the present study is to investigate the effects of sports activity levels on body composition and metacarpal bone development in different pubertal periods. Method:  154 individuals between the ages of 9-13 at different pubertal stages were included in the present study. The voluntary participants comprised of 79 athletes from Istanbul Cerrahpasa University Sports Association and BD Tennis Club with an average age of 10.20±1.25 (years) as the experimental group, and 75 individuals with an average age of 10.70±1.67 ( years), who were admitted to the Istanbul Aydin University, Faculty of Dentistry, Department of Orthodontics, as the control group. The study measured Body Mass Index (BMI), Basal Metabolic Rate (BMR), Body Fat Ratio (BFR%), Body Fat Mass (BFM), Body Fat Free Mass (FFM), Total Body Water (TBW) and Bone Mineral Density (BMD), which constitute the body composition and are considered sub-parameters. Results: The data obtained in the study were analyzed using SPSS 21 package program. In the data, Chi-Square analysis was used to examine the relationship between categorical variables, and t-test for comparison between groups. 0.05 was used as the level of significance. No significant difference was observed in terms of gender between those who are engaged in sports and those who are not (p>0.05). HEIGHT, WEIGHT, BMR, BFM, FFM, TBW measurement averages were significantly higher statistically in those doing sports and a significant difference was found (p0.05). Conclusion: In conclusion, tennis, which is considered among high-impact sports, has been seen to have positive effects on bone structure with regular training.